The dark side of the force : - Hirshleifer, Jack (Cambridge University Press, 2001)
The central tradition of mainline economics deals with only one way of making a living: namely, producing useful goods and services. But there is another way of getting ahead-- through conflict or the "dark side"--that is by appropriating what others have produced. Logically parallel or military aggression and resistance, the dark side includes nonmilitary activities such as litigation, strikes and lockouts, takeover contests, and bureaucratic back-biting struggles. This volume brings the analysis of conflict into the mainstream of economics. Part I explores the causes, conduct, and consequences of conflict as an economic activity. Part II delves more deeply into the evolutionary sources of our capacities, physical and mental, for both conflict and cooperation.